Justice Collaborator dalam Pertimbangan Hakim Memutus Perkara - Fikriyah, Amalina; Masyhar, Ali; Wulandari, Cahya (UI Scholars Hub, 2023)
Justice Collaborator, which refers to the cooperation between a non-primary perpetrator and law enforcement in uncovering organized crimes, is often used to expose cases of extraordinary crimes. The concept of a Justice Collaborator has become a topic of public discussion following the case involving the murder ordered by Ferdy Sambo, where Ferdy Sambo instructed Richard Eliezer to kill Jhosua Hutabarat. Richard Eliezer was found guilty by the court and was designated as a Justice Collaborator.